2020
DOI: 10.1074/jbc.ra119.010540
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the growth factor–binding sequence in the extracellular matrix protein MAGP-1

Abstract: Microfibril-associated glycoprotein-1 (MAGP-1) is a component of vertebrate extracellular matrix (ECM) microfibrils that, together with the fibrillins, contributes to microfibril function. Many of the phenotypes associated with MAGP-1 gene inactivation are consistent with dysregulation of the transforming growth factor β (TGFβ)/bone morphogenetic protein (BMP) signaling system. We have previously shown that full-length MAGP-1 binds active TGFβ-1 and some BMPs. The work presented here further defines the growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 68 publications
2
25
0
Order By: Relevance
“…Together, these findings indicate that TGF‐β mediated by MFAP2 has protective effects on metabolic stress, and lack of TGF‐β could result in metabolic dysfunction in individuals (Craft et al, 2014). In line with this, the biological analysis showed that MFAP2 was able to bind to TGF‐β and BMP via its highly acidic sequence near the N terminus (Broekelmann, Bodmer, & Mecham, 2020). In this study, MFAP2 was found to specifically bind to active TGF‐β1, but not to latent TGF‐β1, and in the absence of MFAP2, active TGF‐β1 did not bind fibrillin, indicating that MFAP2 plays an active role in TGF‐β signaling in the ECM (Broekelmann et al, 2020).…”
Section: The Role Of Mfap2mentioning
confidence: 81%
See 2 more Smart Citations
“…Together, these findings indicate that TGF‐β mediated by MFAP2 has protective effects on metabolic stress, and lack of TGF‐β could result in metabolic dysfunction in individuals (Craft et al, 2014). In line with this, the biological analysis showed that MFAP2 was able to bind to TGF‐β and BMP via its highly acidic sequence near the N terminus (Broekelmann, Bodmer, & Mecham, 2020). In this study, MFAP2 was found to specifically bind to active TGF‐β1, but not to latent TGF‐β1, and in the absence of MFAP2, active TGF‐β1 did not bind fibrillin, indicating that MFAP2 plays an active role in TGF‐β signaling in the ECM (Broekelmann et al, 2020).…”
Section: The Role Of Mfap2mentioning
confidence: 81%
“…In line with this, the biological analysis showed that MFAP2 was able to bind to TGF‐β and BMP via its highly acidic sequence near the N terminus (Broekelmann, Bodmer, & Mecham, 2020). In this study, MFAP2 was found to specifically bind to active TGF‐β1, but not to latent TGF‐β1, and in the absence of MFAP2, active TGF‐β1 did not bind fibrillin, indicating that MFAP2 plays an active role in TGF‐β signaling in the ECM (Broekelmann et al, 2020). Further, increased gonadal fat pad mass and hyperglycemia were also present in Mfap2(−/−) mice at the young age of 2 months, and peaked by 6 months (Walji et al, 2016), indicating a role of MFAP2 in fat metabolism in an age‐dependent manner.…”
Section: The Role Of Mfap2mentioning
confidence: 81%
See 1 more Smart Citation
“…Since neither ELISA nor Western blot analyses using antibodies directed to mature TGF-ß were sensitive enough to detect active TGF-ß1, we used a highly sensitive, cell-based bioassay (Fig. 7 A) that allows detection of human TGF-ß levels as low as 1 pg/ml versus 31.2 pg/ml by the ELISA approach (Beaufort et al 2014 ; Broekelmann et al 2020 ; Johnston et al 2017 ; Tesseur et al 2006 ). Concentrated supernatants from CAMA-1 Rab31 and vector transfectants were left untreated to measure active TGF-ß levels or heated to 65 °C to activate the pool of latent TGF-β in order to allow the determination of the total TGF-ß content.…”
Section: Resultsmentioning
confidence: 99%
“…To measure active TGF-ß, embryonic fibroblasts derived from TGF-ß-deficient mice, and stably transfected with an expression plasmid encoding for the secreted alkaline phosphatase (SEAP) under the control of a Smad2-responsive promoter were used (MFB-F11 cells; [Beaufort et al 2014 ; Broekelmann et al 2020 ; Johnston et al 2017 ; Tesseur et al 2006 ). A density of 2 × 10 4 MFB-F11 cells per well were seeded in 96-well plates (Corning Inc., Corning, NY) and grown for 24 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%